Diagnostic accuracy of plain computed tomography in detecting acute cerebral venous sinus thrombosis keeping magnetic resonance venography as gold standard - Ayesha Tanveer,; Koukab Javed,; Muhammad Zain Arshad,; Yumna Rubab,; Sabahat Tanveer,; Hafiz Zulqarnain,; admin, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the diagnostic accuracy of plain computed tomography using the ratio between hounsfield unit and hematocrit of cerebral venous sinuses in cases of acute cerebral venous sinus thrombosis taking magnetic resonance venography as the gold standard. Method: The cross-sectional validation study was conducted at the Department of Diagnostic Radiology, Combined Military Hospital, Rawalpindi, Pakistan, from March 9 to September 8, 2021, and comprised patients regardless of age and gender presenting with acute neurological and visual signs and symptoms of cerebral venous sinus thrombosis for <5 days. The patients were brain-imaged on 128-slice computed tomography scanner, and the image was assessed and the attenuation values in terms of Hounsfield unit of dural venous sinuses were calculated by taking appropriate region of interest. Haemoglobin and hematocrit values were noted from blood reports, and then the ratio between Hounsfield unit and hematocrit ratio was calculated. Magnetic resonance venography of the patients were performed and the patients were assessed for dural venous thrombosis. Data was analysed using SPSS 23. Results: Of the 201 patients, 98(48.8%) were males and 103(51.2%) were female. The overall mean age was 35.32±19.707 years (range: 1 month-70 years). According to the Hounsfield unit-hematocrit ratio, acute cerebral venous sinus thrombosis was detected in 173(86.01%) patients, while magnetic resonance venography detected 178(88.6%). The Hounsfield unit-hematocrit ratio had sensitivity 91.01%, specificity 52.17% and diagnostic accuracy 86.57%. Conclusion: Computed tomography attenuation value and Hounsfield unit-hematocrit ratioon unenhanced computed tomography could be used as a reliable method to detect acute cerebral venous sinus thrombosis in emergency settings. Key Words: Computed tomography, Acute cerebral venous sinus thrombosis, Magnetic resonance venography.